Directors’ IT expertise and firms’ total factor productivity - Rongli Yuan; Suting Dang; Ruijing Li; Jingyu Gao; Wenyue Jin (China Journal of Accounting Studies)
Using a hand-collected data set of Chinese A-share non-financial listed companies spanning years 2005–2020, this study examines whether directors’ information technology expertise influences firms’ total factor productivity. Our findings indicate a significant and positive effect. The positive effect is more salient for firms with lower capital intensity and firms in non-competitive product markets. Furthermore, two mechanisms through which directors’ information technology expertise improves total factor productivity have been identified: one is the increase in information technology investments; the other one is the enhancement in operating efficiency of fixed assets. Our study not only sheds new lights on the effects of directors’ information technology expertise, but also provides convergent evidence on the determinants of firm-level total factor productivity.